Combining DNA Mini-Barcoding and Species-Specific Primers PCR Technology for Identification of Heosemys grandis - Li, Ping; Li, Dong; Hong, Yuling; Chen, Mingyang; Zhang, Xia; Hu, Liu; Liu, Chunsheng (Frontiers in Ecology and Evolution, 2022)
Heosemys grandis, a species of Asian water turtle, that has a wide range of applications in the food and pharmaceutical industries. Since some processed products cannot be identified exclusively by morphological and microscopic identification, a reliable and quick approach to guarantee authenticity is critical. Thus, we fostered an effective and stable molecular identification system to identify Heosemys grandis based on DNA mini-barcoding and species-specific primers PCR technology. A total of 48 turtle samples from 16 different species were collected. To distinguish Heosemys grandis from its counterfeits, DNA mini-barcoding and a pair of species-specific primers were designed and verified by PCR after analyzing the COI sequences of samples. The results showed that only Heosemys grandis samples could generate a single clear band following amplification using species-specific primers. Employing DNA mini-barcoding to amplify samples can verify authenticity by sequence alignment. These findings indicated that species-specific primers PCR technology combined with DNA mini-barcoding could accurately detect the authenticity of Heosemys grandis. This technology broadens the application of molecular biology techniques in the food and pharmaceutical industries. It provides a reliable and convenient method for identifying raw materials to standardize the market and protect customers’ rights and interests.